Efficacy of Neck-Specific Exercise With Internet Support Versus Neck-Specific Exercise at a Physiotherapy Clinic in Chronic Whiplash-Associated Disorders: Multicenter Randomized Controlled Noninferiority Trial - Gunnel Peterson; Anneli Peolsson (JMIR Publications, 2023)
BackgroundNeck-specific exercises (NSE) supervised by a physiotherapist twice a week for 12 weeks have shown good results in chronic whiplash-associated disorders (WADs), but the effect of exercise delivered via the internet is unknown. ObjectiveThis study examined whether NSE with internet support (NSEIT) and 4 physiotherapy sessions for 12 weeks were noninferior to the same exercises supervised by a physiotherapist twice a week for 12 weeks (NSE). MethodsIn this multicenter randomized controlled noninferiority trial with masked assessors, we recruited adults aged 18-63 years with chronic WAD grade II (ie, neck pain and clinical musculoskeletal signs) or III (ie, grade II plus neurological signs). Outcomes were measured at baseline and at 3- and 15-month follow-ups. The primary outcome was change in neck-related disability, measured with the Neck Disability Index (NDI; 0%-100%), with higher percentages indicating greater disability. Secondary outcomes were neck and arm pain intensity (Visual Analog Scale [VAS]), physical function (Whiplash Disability Questionnaire [WDQ] and Patient-Specific Functional Scale [PSFS]), health-related quality of life (EQ-5D-3L and EQ VAS), and self-rated recovery (Global Rating Scale [GRS]). The analyses were conducted on an intention-to-treat basis and with the per-protocol approach as sensitivity analyses. ResultsBetween April 6, 2017, and September 15, 2020, 140 participants were randomly assigned to the NSEIT group (n=70) or the NSE group (n=70); 63 (90%) and 64 (91%), respectively, were followed up at 3 months, and 56 (80%) and 58 (83%), respectively, at 15 months. NSEIT demonstrated noninferiority to NSE in the primary outcome NDI, as the 1-sided 95% CI of the mean difference in change did not cross the specified noninferiority margin (7 percentage units). There were no significant between-group differences in change in NDI at the 3- or 15-month follow-up, with a mean difference of 1.4 (95% CI -2.5 to 5.3) and 0.9 (95% CI -3.6 to 5.3), respectively. In both groups, the NDI significantly decreased over time (NSEIT: mean change -10.1, 95% CI -13.7 to -6.5, effect size=1.33; NSE: mean change -9.3, 95% CI -12.8 to -5.7, effect size=1.19 at 15 months; P<.001). NSEIT was noninferior to NSE for most of the secondary outcomes except for neck pain intensity and EQ VAS, but post hoc analyses showed no differences between the groups. Similar results were seen in the per-protocol population. No serious adverse events were reported. ConclusionsNSEIT was noninferior to NSE in chronic WAD and required less physiotherapist time. NSEIT could be used as a treatment for patients with chronic WAD grades II and III. Trial RegistrationClinicalTrials.gov NCT03022812; https://clinicaltrials.gov/ct2/show/NCT03022812